KORELASI SHALAT TERHADAP KESEHATAN TUBUH - HERWANI HERWANI (Jurnal Kesehatan, 2024)
Prayer is a form and obligation from Allah SWT to Muslims. By performing prayer, a person can feel closer to Allah SWT directly. Prayer itself must be done with a call from a heart full of devotion, fear and humiliation before Allah, without boundaries of time and space. Praying five times a day is considered an effective form of exercise. The goal is for the overall prayer movement to be calm and repetitive, involving all aspects. These prayer movements relax the joint muscles, maintain the body's energy balance, relax the joint muscles, and improve blood circulation throughout the body, especially to the brain because the brain is at the top, so the heart needs to work harder to send blood to the lower parts. over the brain.